Gel combustion synthesis and characterizations of nanocrystalline ZnO in various dispersants and mol ratio - Razak N.A.A.; Shah N.N.H.; Misran H.; Manap A.; Yap B.K. (2023)
Zinc oxide nanoparticles were successfully synthesized using modified gel combustion synthesis route. Zinc nitrate was used as oxidant while fatty alcohol (8 carbon chains - octyl alcohol) and fatty ester (12 carbon chains - lauric acid) derived from palm oil as well as glycerol played the role of organic dispersants/fuel. X-ray diffraction (XRD) patterns of the calcined samples exhibited three prominent peaks at ca. 2e? = 31.9°, 34.6° and 36.4° corresponding to (100), (002) and (101) reflection planes which were well indexed to zinc oxide hexagonal phase with wurtzite structure. Additional peaks were not observed in XRD patterns suggesting that no other phases were formed during the combustion synthesis. The morphology of calcined samples produced using glycerol as fuel exhibited elongated spindle-like shapes at ca. 1 ìm consisted of nanoparticles. Samples prepared using fatty alcohol as fuel exhibited hexagonal morphology with crystallites sizes of ca. 30 to 40 nm. These results suggested that palm oil derived fatty alcohols and fatty esters are alternative materials as organic dispersants in the production of metal nanoparticles using gel combustion synthesis. The resulting optical properties of ZnO nanocrystallites prepared in this study were similar to those obtain from bulk materials with energy band gap value at ca. 3.28 eV compared to 3.37 eV for the latter. © (2014) Trans Tech Publications, Switzerland.